Effects of hydroxyethyl starch 130/0.42 vs. Ringer's acetate on cytokine levels in severe sepsis. Issue 8 (26th June 2017) - Anthon, C. T.; Müller, R. B.; Haase, N.; Hjortrup, P. B.; Møller, K.; Lange, T.; Wetterslev, J.; Perner, A.
Abstract : Background: The Scandinavian Starch for Severe Sepsis/Septic Shock (6S) trial showed increased 90‐day mortality with hydroxyethyl starch (HES) 130/0.42 vs. Ringer's acetate. To explore the underlying pathophysiology, we compared early changes in plasma cytokine concentrations between patients resuscitated with HES vs. Ringer's acetate. Methods: In a subgroup of 226 patients from the 6S trial, we calculated delta plasma concentrations of tumour necrosis factor alpha (TNF‐α), interleukin (IL)‐6 and IL‐10 from randomization to day 2. We used multiple linear and logistic regression analyses to assess differences between the groups and associations between delta cytokine concentrations and 90‐day mortality, respectively. Results: Baseline characteristics and day 2 mortality were comparable between the groups. We observed similar delta cytokine concentrations in the HES vs. Ringer's group (mean difference in delta TNF‐α: −1.5 pg/ml (95% CI, −4.9 to 1.9), P = 0.39; IL‐6: 36.0 pg/ml (−24.1 to 96.1), P = 0.24; IL‐10: −3.9 pg/ml (−21.1 to 28.9), P = 0.76). In all included patients, we observed a linear relationship between increases in TNF‐α and 90‐day mortality ( P = 0.005). Conclusion: Resuscitation with HES 130/0.42 vs. Ringer's acetate did not appear to affect plasma concentrations of TNF‐α, IL‐6 or IL‐10 differently during the first days after randomization into the 6S trial. In the overall cohort, increases in TNF‐α were associated with increased 90‐day mortality. Although interpretation should be done with caution, it seems unlikely that the increased mortality observed with the use HES in the 6S trial is signalled by early changes in three biomarkers of systemic inflammation.